The influence of internal marketing strategies on organizational employees retention? A case study in the touristic sector - Romana, Fernando; Gestoso, Carlos (Edelweiss Applied Science and Technology, 2024)
This study aims to understand the influence of internal marketing practices on employee’s retention at the Jupiter Marina Hotel (JMH), a hotel unit belonging to the Jupiter Hotel Group. Through a hybrid investigation approach (quantitative and qualitative). Talent retention is achieved based on the conceptual model. By comparing the two types of investigation, it is evident that internal marketing practices have a significant impact on talent retention, measuring it through concepts such as satisfaction, engagement, and commitment. Thus, the conclusion is reached that through the good practice of these three concepts, the impact on talent retention at JMH is of great magnitude, with most of its team being constituted through their return to the organization.